ANALISIS SEMIOTIKA JOHN FISKE TENTANG INSECURE TERHADAP STANDAR KECANTIKAN PEREMPUAN DALAM FILM IM PERFECT - Kartika Khairana; Abdul Rasyid (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The rapid development of today's communication media, film has become a medium that conveys information in a unique way. Related to the film Imperfect (Career, Love & Scales) which was directed by Ernest Prakasa, it provides a discussion about the standard of female beauty in society and the people around it. The main character Rara in the film Imperfect (Career, Love & Scales) experiences related demands from women's beauty standards that make Rara feel insecure about her beauty. The purpose of this study is to describe how to deal with insecurity about the beauty standards that apply in the surrounding environment in the film Imperfect (Career, Love & Scales) for the main character Rara. This study uses descriptive qualitative research methods with John Fiske's semiotic theory to understand the meaning of the reality level at the representational level at the ideological level. The results of this study indicate that there is a feeling of insecurity due to physical conditions that are not in accordance with applicable beauty standards and make peace with Rara's insecurity. Finally, Rara, in the main character of the film Imperfect (Career, Love & Scales), who previously felt insecure about herself, tried and was determined to be like a beautiful woman and have an ideal body, now she proves her determination through the changes in herself that she has always wanted. to be a woman with standard beauty in general. Now he can accept and make peace with himself and love himself well.